Response of the Anaerobic Methanotrophic Archaeon Candidatus “Methanoperedens nitroreducens” to the Long-Term Ferrihydrite Amendment - Cai, Chen; Ni, Gaofeng; Xia, Jun; Zhang, Xueqin; Zheng, Yue; He, Bingqing; Marcellin, Esteban; Li, Weiwei; Pu, Jiaoyang; Yuan, Zhiguo; Hu, Shihu (Frontiers in Microbiology, 2022)
Anaerobic methanotrophic (ANME) archaea can drive anaerobic oxidation of methane (AOM) using solid iron or manganese oxides as the electron acceptors, hypothetically via direct extracellular electron transfer (EET). This work investigated the response of Candidatus ‘Methanoperedens nitroreducens TS’ (type strain), an ANME archaeon previously characterized to perform nitrate-dependent AOM, to an Fe(III)-amended condition over a prolonged period. Simultaneous consumption of methane and production of dissolved Fe(II) were observed for more than 500 days in the presence of Ca. ‘M. nitroreducens TS’, indicating that this archaeon can carry out Fe(III)-dependent AOM for a long period. Ca. ‘M. nitroreducens TS’ possesses multiple multi-heme c-type cytochromes (MHCs), suggesting that it may have the capability to reduce Fe(III) via EET. Intriguingly, most of these MHCs are orthologous to those identified in Candidatus ‘Methanoperedens ferrireducens’, an Fe(III)-reducing ANME archaeon. On the other hand, the population of Ca. ‘M. nitroreducens TS’ declined and was eventually replaced by Ca. ‘M. ferrireducens’, implying niche differentiation between these two ANME archaea in the environment.